Problematik Pembelajaran Daring Pada Masa Pandemi Covid-19 Siswa Sekolah Dasar - Jaenullah, Jaenullah; Nurlaili, Nurlaili; Zaini, Muhammad; Setiawan, Dedi (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to find out the problems of learning carried out remotely or online for elementary school students in Adiwarno Village, Batanghari District, East Lampung Regency. Methods This research used a qualitative approach and the informants in this study were elementary school students, parents of elementary school students and elementary school teachers. Data were collected through interviews. This study concludes that: learning that is carried out remotely or commonly referred to as online learning has a negative impact as well as a positive impact on students, teachers and even parents. Not a few students complain about being bored in online learning, teachers complain about ineffective learning and parents complain about being unprepared to accompany their children to study at home.